Unveiling microbial diversity in slightly and moderately magnesium deficient acidic soils - Munmun Dash; Subramaniam Thiyageshwari; Duraisamy Selvi; Haina K. V. Johnson; Manikandan Ariyan; Karuppusamy Rajan; Rangasamy Anandham (Scientific Reports)
Abstract Magnesium (Mg) an essential plant nutrient is widespread deficient in the acidic soils of Nilgiris of Tamil nadu, India. The vegetable yield and quality is especially affected due to deficiency of nutrients like Mg. This study investigates soil characteristics and bacterial diversity in the Nilgiris district of Tamil Nadu, India, with respect to Mg deficiency. The soil samples were collected from different vegetable growing regions of the Nilgiris to assess soil physiocochemical parameters, soil enzymes and soil Mg status. 16S rRNA gene-based metagenomic analysis used to investigate the functional potential and structural diversity of the bacterial communities in high Mg and low Mg deficiency soil. Results indicated mildly acidic soils with a sandy loam texture and high organic carbon content. While nitrogen (N), phosphorus (P), and potassium (K) levels were adequate, Mg deficiency was consistent. Soil enzymes such as dehydrogenase, acid phosphatase, urease and aryl sulfatase, varied across the soil samples. Additionally, 16S rRNA gene-based metagenomics analysis revealed the bacterial diversity and functional pathways in soils with high and low Mg deficiency. Low Mg levels were associated with increased bacterial richness, dominated by Proteobacteria, Gemmatimonadetes, Actinobacteria, Bacteroidetes, and Acidobacteria. Functional pathways related to carbon metabolism, amino acid biosynthesis, and various metabolic processes were more abundant in low Mg deficient soils. This research highlights the significant influence of Mg levels on bacterial diversity and functional potentials in acidic soils, providing insights into soil management strategies in Mg-deficient regions.